The given expression is-
[tex]-2|2.2x-3.3|=6.6[/tex]First, we divide the equation by -2.
[tex]\begin{gathered} \frac{-2|2.2x-3.3|}{-2}=\frac{6.6}{-2} \\ |2.2x-3.3|=-3.3 \end{gathered}[/tex]Now, we rewrite the absolute value equation in two more equations
[tex]\begin{gathered} 2.2x-3.3=-3.3 \\ 2.2x-3.3=-(-3.3) \end{gathered}[/tex]Let's solve each of them
[tex]\begin{gathered} 2.2x-3.3=-3.3 \\ 2.2x-3.3+3.3=-3.3+3.3 \\ 2.2x=0 \\ x=\frac{0}{2.2}=0 \end{gathered}[/tex]The first solution is zero.
[tex]\begin{gathered} 2.2x-3.3=-(-3.3) \\ 2.2x-3.3=3.3 \\ 2.2x-3.3+3.3=3.3+3.3 \\ 2.2x=6.6 \\ x=\frac{6.6}{2.2}=3 \end{gathered}[/tex]The second solution is 3.